Micro Environmental Change in Various Form Land Cover Revegetation - Dadan Mulyana; Sri Wilarso Budi R; Basuki Wasis; Arum Sekar Wulandari (Jurnal Manajemen Hutan Tropika, 2011)
Evaluation of land rehabilitation (revegetation) activities is necessary for measuring the extent of success of the ongoing activities in rehabilitating and recovering degraded lands. One way for evaluating the success of land rehabilitation (revegetation) is by determining the changes of micro enviroment. The objective of this research was to study the changes of micro environment in various types of revegetated land cover, including scrub/bush land (SB), agricultural land (TP), monoculture teak (JM) and mixed crops (TC) in Ciliwung upper watershed. Research results showed that the highest air temperature and soil temperature were obtained at SB, respectively at 32.8 °C and 26.5 °C, and the lowest at TC, respectively at 28.1 °C and 20.7 °C. Relative humidity and soil moisture were highest at TC (72.3% and 96%) and lowest at SB (60.8%), and the lowest soil moisture occurred at JM (45%). The highest infiltration rate occurred on TP (475.5 mm h-1, very rapid), followed by JM (117 mm h-1, fast) and TC (80 mm h-1), and the lowest at SB (17.65 mm h-1, medium slow). Erosion reductions occurred after 6 years of the revegetation activities with the following results:TC (96,676.1 ton year-1 ha-1), JM (10,790 ton year-1 ha-1), TP and SB (52,867.9 ton year-1 ha-1 and 24,612.6 ton year-1 ha-1). The micro environments for all land cover types were better after revegetation activities.